Pengaruh Reward dan Pengembangan Karir Terhadap Kinerja Pegawai Sektor Publik Kantor Pelayanan Pajak (KPP) Pratama Gubeng, Surabaya - Bernadus Haba; Waloyo (CV. Muris Global Education, 2026)
This study aims to analyze the influence of rewards and career development on the performance of public sector employees at the Tax Service Office (KPP) Pratama Gubeng, Surabaya. The research approach used is quantitative with a data collection method through questionnaires. The population in this study was 126 employees, with a minimum number of samples analyzed as many as 96 respondents using accidental sampling techniques. Data analysis was carried out by multiple linear regression using the help of the SPSS version 25 program. The results of the study showed that partially, rewards did not have a significant influence on employee performance. On the contrary, career development has been shown to have a positive and significant influence on employee performance. However, simultaneous testing showed that rewards and career development together had a positive effect on the performance of employees of KPP Pratama Gubeng, Surabaya. The Adjusted R Square value showed that the two variables contributed 33% to the variation in employee performance, while the remaining 67% were influenced by other factors outside the study.